Pelatihan dan Pengabdian Penggunaan QRIS Terhadap UMKM Berusia Lanjut 40-60 Tahun atau Masyarakat Awam di Era Digitalisasi Desa Sukadami Kecamatan Cikarang Selatan - Dara Julita; Etty Zuliawati Zed; Fazrya Rauf; Auliya Putri Mardiah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The current digitalization era makes people adapt to technological developments, including in terms of payment transactions. Quick Response Code Indonesian Standard (QRIS) has emerged as a practical and simple digital payment solution, but for MSMEs, especially the elderly (4060 years) or the general public, there are still many challenges. This service aims to evaluate the effectiveness of training and community service in increasing the use and understanding of QRIS among elderly MSMEs and the general public in Sukadami Village, South Cikarang District. Through participatory training methods and quantitative approaches, this study measures the impact of the service program on digital literacy and the level of QRIS adoption.